On the response of a person to a verbal call for action - Elijošiūtė, S. (Psichologija, 1968)
During an incentive conversation, the promoter seeks to achieve a certain response during verbal communication. The promoter uses a certain entirety of socially accepted linguistic means (lexical, grammatical, syntactical, intonation) as a means, i.e. uses one of the incentives in a relevant language (order, command, request, suggestion, etc.). Application of one or other incentive is determined by a number of communication conditions. One of such conditions is the anticipated response of the addressed person to a certain linguistic effect. The response of the addressed person depends on a number of factors, some of them are briefly reviewed: l) motivation, involving action to be performed by the addressed person, into activity characterized by a certain motive; 2) contradiction (or its absence) between what is necessary for the performance of a certain action and what can be possibly done by the motivated person (assessment from the point of view of the addressed person); 3) congruity of the produced incentive with the anticipated response from the point of view of notional, linguistic, physical expression, and perception qualities. Denominations of possible responses of the stimulated person to a linguistic impact can be found in linguistic (particularly, in lexical) material, because language reflects all social-historical experience of a certain linguistic community. The entirety of possible denominations of responses produced by the addressed person can be hypothetically classified according to the degree of resistance by the addressed person, into four groups (expressions of disobedience, abstinence, submission and initiative). Degree of change in the response of the motivated person, influencing the action of the promoter, shall be established by means of experiment.